2020
DOI: 10.1016/j.envpol.2019.113637
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of organic plastic additives in surface waters of the Rhône River (France)

Abstract: We present here a comprehensive study (1-year regular sampling) on the occurrence of major families of organic plastic additives in the Rhône River surface waters. Potential sources and contaminant export are also discussed. A total of 22 dissolved phase samples were analyzed for 22 organic additives mainly used in the plastic industry, including organophosphate esters (OPEs), phthalates (PAEs) and bisphenols (BPs). Our results indicate that PAEs were the most abundant class, with concentrations ranging from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(24 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…For organic plastic additives in MP, thermal analysis is recommended. On the other hand, chemical extraction has been well developed in recent years for these compounds [141][142][143] .…”
Section: Challenges Of Nanoplasticsmentioning
confidence: 99%
“…For organic plastic additives in MP, thermal analysis is recommended. On the other hand, chemical extraction has been well developed in recent years for these compounds [141][142][143] .…”
Section: Challenges Of Nanoplasticsmentioning
confidence: 99%
“…In addition, both atmospheric (Castro-Jiménez et al, 2017) and riverine inputs of organic contaminants (Schmidt et al, 2019;Castro-Jiménez et al, 2019) have been reported in the area. Indeed, a recent study showed that PAEs and OPEs are transported by the Rhône River surface waters (Schmidt et al, 2020). The main objectives are; i) to determine the environmental concentrations of PAEs and OPEs in sediments affected by different anthropogenic signatures; ii) to discuss their spatial distribution in the Gulf of Lion; iii) to explore the role of the Rhône River in delivering PAEs and OPEs associated with its sedimentary inputs in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of plastics in the environment has wide negative effects on living organisms. Currently, additives leached from plastics are present in the environment ( Sackaria and Elango, 2020 , Schmidt et al, 2020 ). Beside the additives with toxic effects, which can be released and get to water or soil, microplastics can be ingested for instance by marine species and release toxins directly into the body ( Alomar et al, 2017 , Du et al, 2020 , Koongolla et al, 2020 , Ozturk and Altinok, 2020 ).…”
Section: Future Risk and Challengesmentioning
confidence: 99%